2007
DOI: 10.1530/eje-06-0716
|View full text |Cite
|
Sign up to set email alerts
|

Circulating nerve growth factor levels in relation to obesity and the metabolic syndrome in women

Abstract: Objective: Neurotrophins (NTs) could be involved in the development and progression of inflammatory and immune diseases. Because obesity and the metabolic syndrome (MetSyn) are related to a lowgrade systemic inflammation, plasma NT levels (neurotrophinemia) could play an important role in the ethiopathogenic mechanisms underlying these metabolic derangements. This is the first study evaluating the plasma NT levels in a group of women with obesity and MetSyn, and also the adipose tissue nerve growth factor (NGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
81
1
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(96 citation statements)
references
References 45 publications
9
81
1
5
Order By: Relevance
“…The increase in TNF-α and IL-6 serum levels in MetS also play a role in the pathogenesis in psoriasis patients (2)(3)(4)(5)(6)(7)29). TNF-α and IL-6 serum and tissue levels were similar in all three groups in our study.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The increase in TNF-α and IL-6 serum levels in MetS also play a role in the pathogenesis in psoriasis patients (2)(3)(4)(5)(6)(7)29). TNF-α and IL-6 serum and tissue levels were similar in all three groups in our study.…”
Section: Discussionsupporting
confidence: 64%
“…Tumor necrosis factor-α (TNF), interleukin-1β (IL), IL-6, IL-8, IL-10, haptoglobulin, leptin and adiponectin are secreted from adipose tissue and initiate inflammation by passing into the circulation. The neurotrophins (NTs) are composed of nerve growth factor (NGF) and brain-derived neurotrophic factor (BDNF), NT-3, NT-4 and NT-5 and are believed to be associated with inflammatory diseases as well as MetS (4,5). In recent studies, NTs have been reported to be effective not only on the peripheral and central nervous system but also on the immune and endocrine systems (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Such a role in adipocytes remains to be explored. However, NGF and the receptor p75NTR/sortilin are produced by adipose tissue [36,47], and both circulating NGF [48] and sortilin levels (present study) are modified in obesity. Sortilin is also the neurotensin-3 receptor, but the physiological role of this neurotensin-activated pathway is not fully understood [38].…”
Section: Discussionmentioning
confidence: 50%
“…NGF는 뉴런 의 목표에 의해 분비되는 단백질이며, 교감 및 감각뉴런 유지 와 더불어 세포성장을 포함하는 생물학적 활동에 중요한 역할 을 담당한다 [31]. 그리고 최근 염증반응과 면역계통 질환의 진 행에도 관여하는 것으로 보고되고 있다 [3]. 선행연구에 의하면 혈장 NGF 수준은 고도 비만인 경우 낮게 나타나며, 또한 염증 요인, BMI, 체지방율 그리고 허리둘레와 높은 상관을 가지고 있다 [3].…”
Section: 서 론unclassified
“…선행연구에 의하면 혈장 NGF 수준은 고도 비만인 경우 낮게 나타나며, 또한 염증 요인, BMI, 체지방율 그리고 허리둘레와 높은 상관을 가지고 있다 [3]. NGF는 갈색 지방세포에서 합성되어 분비되므로 유 전적으로 마른 동물모델 보다는 비만 동물모델에서 높게 나타 난다고 최초로 밝혔지만, 연령에 따라 차이가 존재한다고 하 였으며 [20], 인간을 대상으로 한 연구에서 성인의 경우 정상체 중보다는 비만인의 NGF가 높고 [3], 고도비만보다는 과체중인 피험자의 NGF가 더 높게 나타났다고 하여, 비만 수준과 연령 에 따라 차이를 보이고 있어 조직수준에서의 연구가 절실히 필요하다. 한편, BDNF는 뇌뿐만 아니라 말초에서도 발견되는 단백질 로서 중추신경계와 말초신경계의 특정 뉴런에서 활성 되어 뉴런이 생존하는데 지원해주는 역할을 한다.…”
Section: 서 론unclassified